Knowledge of surgical informed consent and associated factors among patients undergone obstetric and gynecologic surgery at Jimma Medical Center, Jimma, Ethiopia, 2020: an institutional based cross-sectional study - Belete Fenta Kebede; Tsegaw Biyazin Tesfa; Aynalem Yetwale Hiwot; Yalemtsehay Dagnaw Genie (Perioperative Medicine, 2023)
Abstract Introduction Informed consent is the process whereby a patient makes a voluntary decision about their medical and surgical care with knowledge of the benefits and potential risks. Poor informed consent processes may increase potential for medical errors and malpractice. Little is known of the knowledge of surgical informed consent with regard to their surgical treatment in Ethiopia. Therefore, this study aimed to assess the knowledge of surgical informed consent and associated factors among patients who underwent obstetric and gynecologic surgery at Jimma Medical Center, Jimma, Ethiopia. Methods and materials An institution-based cross-sectional study was conducted from April 1 to May 30, 2020, among 404 women undergo obstetric and gynecologic surgery at Jimma Medical Center. Data were collected through a face-to-face interview using a structured questionnaire. The collected data were coded, entered into Epi data version 3.1, and analyzed using SPSS version 25. Bivariate and multivariate regression analyses were performed to determine the association between an outcome variable and an independent variable. Tables, pie-charts, and texts were used to report the result. Results Of 404 patients sampled, only 372 women were agreed and participated in the study and gave response rate of 92.1%. The respondent satisfaction level (AOR 1.823 (95%CI 1.061–3.134)) and patient to provider relationship (AOR 0.472 (CI 1.217–3.697)) were associated with knowledge of surgical informed consent. Conclusion The overall level of knowledge regarding informed consent for surgerywas significantly lower than that of other national and international figures. Patient satisfaction and patientto provider relationships were associated with knowledge of surgical informed consent. Adequate information should provide before surgery to improve patients’ knowledge regarding surgical informed consent and to improve the consent process to make it better suited to fit the needs of all patients.